Existential-legal principle in forming the personality of a human and citizen - V. V. Lazarev (Russian Journal of Economics and Law)
Objective: to study the existential-legal principle in the formation of the personality of a human and a citizen.Methods: the dialectical approach to the cognition of social phenomena led to the choice of the following methods of cognition: formal-logical, comparative-legal, sociological methods.Results: scientiﬁc usage includes a methodologically dubious approach associated with the concept of “a person in law”. There seems to be a human and a citizen in law. In this regard, of the most important doctrinal issues referring to a human, attention is drawn by the issue of the role of the existential principle in the formation of the personality of a human and a citizen, which has not been developed by lawyers. Existence covers situations of personal choice that affect the vital problems of a person’s life, their formation as a personality, overcoming objective life difﬁculties and subjective dissatisfaction in the process of experiencing them. The level of freedom, felt (reﬂected) by a person and allowing them (giving them the right) to decide for themselves what to do with their life in all its senses, forms an existential right. It is still waiting for its researcher. One of the directions of such research is the formation of subjective rights and obligations outside and before the mediation of relevant social relations by positive law.Scientiﬁc novelty: the most important existentialist questions (where we came from, where we are going, what we stand on, what justiﬁes us, what is the meaning of our presence in the world) are not only philosophical questions. They are purely practical. It is no coincidence that discontent is brewing in the Russian public opinion, both in the scientiﬁc community and in the mass of thinking citizens, about the lack of a basic ideology. Existentialism gives preference to internal regulators of behavior over external ones and, consequently, this philosophy does not leave much room to legalism and everything related to the use of legislative means. However, the study of the existence involved in the legal sphere, directed to the legal status of the individual, inevitably actualizes the problems of legislative regulation, evaluation of the existing laws for compliance with natural rights and obligations. The aspect which always remains relevant is the prevention of behavior that deviates from the requirements of an external regulator through metered prohibitions and permits of legitimate authorities. The place of the existential principle in the formation of the personality of a human and a citizen is determined in the light of the ratio of general, special and individual spheres, patterns and forms of life activity. The ﬁrst is dominated by the general laws of natural-scientiﬁc and social development reﬂected in philosophy; the second is dominated by the speciﬁc laws of the political and legal movement of societies and states in a deﬁnite place and time; the third – by the existence of active personalities.Practical signiﬁcance: the conclusions and provisions of the article can be used in scientiﬁc and legislative activities, in the educational process of universities.